1986
DOI: 10.1021/ma00165a021
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of radiation-cured networks

Abstract: Simultaneous cross-linking and chain scission reactions that are induced by ionizing radiation have been simulated with a computer. These studies were performed for both bulk-and solution-cured poly(dimethylsi1oxane) (PDMS) systems. Variations of network structures and mechanical properties that depend on the degree of cross-linking are presented. It is shown that radiation-cured networks are barely connected and contain large amounts of defect structures. More than 90% of the defects are found to be dangling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…is small in the gels which they use for experiment. However, computer simulations of the radiative crosslinking process by Sly and Eichinger [35] suggest that the presence of pendant chains, the formation of short wasted loops, and the scission of chains are all important factors. The scattering of a network which contains a large fraction of unstrained chains due to this type of defect would obviously be expected to be much closer to the unstrained network scattering.…”
Section: The Phantom Networkmentioning
confidence: 99%
“…is small in the gels which they use for experiment. However, computer simulations of the radiative crosslinking process by Sly and Eichinger [35] suggest that the presence of pendant chains, the formation of short wasted loops, and the scission of chains are all important factors. The scattering of a network which contains a large fraction of unstrained chains due to this type of defect would obviously be expected to be much closer to the unstrained network scattering.…”
Section: The Phantom Networkmentioning
confidence: 99%
“…Recently, molecular dynamics (MD) simulation has been widely applied in many different fields, and has provided information about microscopic pictures of network structure. 26,31,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In the present study we use MD simulations to reproduce the swelling/deswelling of a polymer network after preparation. We have already reported that our MD simulation can produce realistic network structure for tetra-PEG gels.…”
Section: Introductionmentioning
confidence: 99%
“…26,31,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In the present study we use MD simulations to reproduce the swelling/deswelling of a polymer network after preparation. The Obukhov-Rubinstein-Colby model depicts the influence that swelling/deswelling has on elasticity, but its physical picture is too complicated to be sufficiently validated by experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The modern theory of real networks now permits a more accurate determination of network structures through use of equations (84), (87), and (95) (187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204). Stress-strain measurements can be analyzed as shown in Figure 17.…”
Section: Determination Of the Degree Of Cross-linking By Stress-straimentioning
confidence: 99%